Multiplex Reverse Transcription-PCR Assay for Detection of Type A Influenza Virus plus Differentiation of Avian H7 and H9 Hemagglutinin Subtypes in Iran - E Saberfar; A Najafi; Z Goodarzi; H Lashini (Tehran University of Medical Sciences, 2009)
"nBackground: Avian influenza virus (AIV) infection is a major cause of bird and human morbidity and mortality. We aimed to evaluate a specific and sensitive multiplex RT-PCR that can simultaneously detect influenza type A viruses and differentiate the two most important subtypes of avian influenza viruses H7 and H9 subtypes."nMethods: A multiplex reverse transcriptase-polymerase chain reaction (mRT-PCR) was developed and optimized for the detection of type A influenza virus. Simultaneously avian H7 and H9 hemagglutinin subtypes was differentiated. Three sets of specific oligonucleotide primers were used in this test for type A influenza virus, H7 and H9 heamagglutinin subtypes."nResults: The mRT-PCR DNA products were visualized by gel electrophoresis and consisted of fragments of 313 bp for H7 and 428 bp for H9 hemagglutinin subtypes, and 101 bp for type A influenza virus. The common set of primers for type A influenza virus were able to amplify a 101 bp DNA band for any of the other subtypes of influenza A virus."nConclusion: The mRT-PCR assay developed in this study was found to be sensitive and specific.  No specific amplification bands of the same sizes (313 and 428 bp) could be amplified for RNA of other influenza hemagglutinin subtypes, nor specific amplification bands of type A influenza (101 bp) for Influenza B, C, or other viral or bacterial pathogens tested in this study.